L’autre du prophétisme congolais - Patrice Yengo (Continents manuscrits)
« For me, one can be a writer only as a poet » assured Sony Labou Tansi, but can one seriously be a poet in the Congo without being a prophet ? This is the question that this paper tries to answer. Poet and prophet ; these two propositions connect Sony, not to the scriptural prophetism described by Jean-Loup Amselle in Branchements but, to a history of Congolese prophetism pertaining to the moyo (Belly) and its disappointment following the failure of the meeting between the kongolese Kingdom with Portugal and Christianity in the sixteenth century. The Word in Sony’s poetry is a discourse of emanations and visions that seeks to keep alive and dynamic the relationship to the Kongo. By tieing the Scriptural requirement down to this historical depth, his poetry accords the present with the past but attests also to faith in an appropriation of the world that makes sense only as a presentation of « the up-coming ». From the beginning of his writing, with, his Youth poems, he is caught by this call and tight fitted in the corset of the prophet he seeks to get rid of. We almost hear him saying these Gospel words : « No, I am not worthy, O Lord, but only say a word and my soul will be healed ». Except that the Word is him to wear it. It is this mission against which he is struggling that I try to restitute in this text before finding him a due place in the Kongo prophetic filiation.